OPTIMIZATION RESULTS OF TEMPOROMANDIBULAR REPARATIVE REGENERATION BY NITINOL MATRICES (Experimental study) - N. M. Dyuryagin; S. S. Stepanov; V. V. Semchenko; V. E. Gunter; E. N. Dyuryagina (Вестник трансплантологии и искусственных органов, 2014)
Aim. Through the experiments on animals, mandibular fragments reparative regeneration and osteohistogenesis in the post-resection period using different ways of their optimization by artifi cial nitinol matrices were investigated.Materials and methods. Rabbits (two groups) were subjected to similar resections of mandibular right branch fragments with articular head exarticulation. In the fi rst group (n = 10) extrafocal matrix structures placement option towards regeneration foci (sagittal dislocation) was used, in the second one (n = 10) intrafocal matrix bone and periosteum nitinol constructions placement option was used.Results. In the fi rst group, the following reconstructive results were received: organ-like osteogenic regenerates fully displaced mandibular defects in 12 months. In the second group reconstructive results were the following: tissue-engineered composites fully displaced mandibular defects in 3 months. Biological, biometric, radiological, histological, immunohistochemical, morphometric, statistical methods were used to evaluate the results.Conclusion. Reparative regeneration and osteohistogenesis at extrafocal placement of artifi cial matrix structures are able to reconstruct independently mandibular fragments due to natural regeneration. Reparative regeneration and osteohistogenesis at intrafocal placement of artifi cial matrix structures are able to reconstruct independently mandibular fragments due to bone and periosteum tissue-engineered composites forming. Four-fold advantage of mandibular reconstruction dynamics by tissue-engineered composites being equal in functional effi ciency with natural regeneration results testifi es to their availability for usage in clinical practice.